Reducing Metabolic Syndrome Risk Using a Personalized Wellness Program. Issue 12 (December 2015) - Steinberg, Gregory; Scott, Adam; Honcz, Joseph; Spettell, Claire; Pradhan, Susil
Abstract : Objective: The aim of this study was to determine the impact of a targeted, personalized wellness program on reducing employees' future risk of metabolic syndrome. Methods: Aetna piloted a year-long program that included a limited genetic profile, a traditional psychosocial assessment, and high-intensity coaching in a randomized controlled study of Aetna employees with an increased risk for metabolic syndrome. Results: Sustained employee engagement of 50% over the course of 1 year; 76% of participating employees lost an average of 10 pounds (4.5 kg) ( P < 0.001 vs baseline weight), and there were trends in improved clinical outcomes relative to three of five metabolic factors. Average health care costs were reduced by 122 per participant per month, resulting in a positive return on investment in the program's first year. Conclusions: At scale, such programs would be expected to lead to significant downstream reduction in major clinical events and costs.